(untitled) (CAHIERS MAGELLANES-NS, 2024)
Adventure tourism has emerged as a dynamic and exciting niche within the travel industry, offering travelers immersive experiences in rugged landscapes and off-the-beaten-path destinations. Economically, adventure tourism contributes significantly to local economies by creating employment opportunities, promoting local culture, and stimulating infrastructure development. However, this growth also presents environmental challenges, such as habitat disruption and increased carbon footprints, requiring sustainable practices and policies. This review paper delves into the multifaceted dimensions of adventure tourism, exploring its characteristics, motivations, impacts, and prospects. Drawing upon a synthesis of academic literature, industry reports, and case studies, this paper aims to comprehensively understand adventure tourism and its evolving role in the global travel landscape.